KOMPARASI ANTARA POLYMERASE CHAIN REACTION (PCR) DAN LOOPMEDIATED ISOTHERMAL AMPLIFICATION (LAMP) DALAM DIAGNOSIS MOLEKULER - Anggun Feranisa (Faculty of Dentistry, Universitas Islam Sultan Agung, 2016)
Background: Molecular diagnostic is an emerging diagnostic method inpersonalized medicine/dentistry era. Usually, it uses nucleic acid amplificationmethod to detect various diseases. PCR is conventional nucleic acid amplification method. However, due to an urgency in infectious diseases’ diagnotic method, scientists developed LAMP as new nucleic acid amplification method.Discussion: There are various experiments used to develop LAMP as infectious diseases diagnostic method compared to PCR. The results are LAMP more sensitive, specific, rapid, and inexpensive than PCR.Conclusion: Both PCR and LAMP can be used as molecular diagnostic tools.LAMP prefer to used as infectious disease diagnostic method in poor anddeveloping countries.